Training early childhood teachers integrating project approach with multicultural education in the classroom - Hakoon, Vannisa; Tanunchaibutra, Prin; Kuroda, Ariyabhorn (Journal of Education and Learning (EduLearn), 2025)
This research aimed to examine the improvement of teachers’ abilities to integrate the project approach with multicultural education. A total of three female teachers from a kindergarten in the northeastern region of Thailand participated in this research. The research procedure began with the three teachers developing lesson plans. This was followed by each teacher teaching the lesson to their peers who played the role of learners in an early childhood classroom. The researchers utilized field notes as an instrument to collect data during the lesson plan workshop and peer teaching. Finally, the researchers used a conservation guide as another instrument to collect verbal data through reflections upon the workshop and peer teaching. The results revealed that teachers faced challenges in developing lesson plans including defining objectives, creating content maps, designing learning activities, and finding materials and resources. On top of that, the results regarding peer teaching indicated that teachers are not familiar with project approach thus they are facing difficulties in facilitating learning activities and classroom management. The overall results have contributed to the field of early childhood teacher professional development.